SOCIAL ENGINEERING ATTACKS AND PROTECTION AGAINST THEM: SITUATION, PROBLEMS AND SOLUTIONS IN UZBEKISTAN - Shukurov Orzikul Pardayevich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This scientific article analyzes modern manifestations of social engineering attacks, their prevalence in the cyberspace of Uzbekistan, and the harmful consequences they cause to society and organizations. During the study, methods such as phishing, smishing, vishing, deceiving users through malicious links, and fraud related to bank cards were studied. The main causes of social engineering attacks, vulnerabilities associated with the human factor, and technical, organizational, and legal solutions to reduce them are proposed.